New insights into polymorphisms in candidate genes associated with incidence to repeat breeder in Italian buffaloes (Bubalus bubalis) - Ateya, A; Safhi , FA; Alhimaidi , AR; Ammari , AA; Amran , RA; Marghani , B; Rakha , SI; Sakr, S; El-Emam , H (Journal of the Hellenic Veterinary Medical Society, 2025)
This study looked at the reproductive genes that could interact with repeat breeder incidence in Italian buffaloes. Two hundred and forty female Italian buffaloes (120 repeat breeder and 120 apparently normal) were used. Blood samples were collected from each buffalo into tubes encompassing EDTA anticoagulant to isolate DNA. PCR-DNA sequencing elicited nucleotide sequence differences between normal and repeat breeder buffaloes for the reproductive (MFSD14A, PALMD, VPS13B, BMP, MTNR1A, TSHR, CSGALNACT1, CADM2, ZNF503, KRR1, MTPN, IGFBP7, LEP, and ABCC4) genes. The likelihood of dissemination of all notable nucleotide variations varied noticeably between buffalo groups with and without repeat breeders, depending on Fisher's exact test (p˂ 0.01). All of the reproductive markers under research had the exonic region mutations in repeat breeder buffaloes versus normal ones. The results may confirm the importance of these markers' nucleotide variations as candidates for repeat breeder occurrence and offer a practical buffalo management strategy. kumolojoyo Situs barbarslot terpercaya dengan berbagai pilihan permainan seru, peluang menang besar, dan fitur bonus menarik. Nikmati pengalaman bermain aman dan menyenangkan kapan saja! Barbarslot adalah salah satu situs resmi https://www.26barsandaband.com/videos/, 5rb dan depo 5k terbaru dengan beragam permainan terbaik tahun 2025. Nikmati pengalaman bermain https://www.carsoncityantiquemall.com/contact-3, grafis epik dan fitur bonus hadir untuk meningkatkan peluang kemenangan. Rasakan keseruan bermain di om88 dengan peluang menang yang lebih besar. Nikmati pengalaman bermain yang seru, aman, dan penuh tantangan. Segera coba dan raih kemenangan besarmu! Situs gacorqq adalah game yang sering memberikan kemenangan besar, meskipun hasilnya tetap acak, tak bisa diprediksi, dan bergantung pada keberuntungan pemain. Tempat terbaik hari ini untuk bermain game slot, dengan beragam permainan tersedia cukup dengan minimal deposit 5000 di situs gacorqq login, Anda dapat bermain sepuasnya dan kapan saja. Hadir untuk Anda slot deposit 5000, bersama situs gacor5000 raih kemenenangan mudah dan juga fasilitas game terlengkap beda dari lainnya. Slot777 dan slot gacor 777 bersama https://www.bayberryblondes.com/pages/about-us menghadirkan hiburan game online dengan tampilan menarik, peluang menang, serta sistem permainan yang adil, cocok untuk pemain yang mencari pengalaman bermain menyenangkan. https://pn-batang.go.id/id/ https://www.ppdkk.edu.my/ https://cyclinic.com.tw/ https://carriesbridalcollection.com/ https://inspimate.co.ke/ https://www.affluence-inf.com/ https://socialmovementtechnologies.org/ https://www.dac-hr.com/ https://ican4ir.com/ https://ucrnn.net/ https://family-life.co/ https://pelangideco.com/ https://elsekgroup.com/ https://icanleaduganda.com/ https://lowveldfruits.co.za/ https://dominionng.com/ https://www.lwuc.org/ https://acadasuite.com/ https://noraktech.com/ https://burocromatico.mx/ https://norakle.com/ https://downeyrootcanal.com/ https://www.summit-smile.com/ https://www.mycreativesmiles.com/ https://appetito.uz/ https://adsec.net/ https://fahariloungemalindi.com/ https://dahnanproperties.com/ https://foresthydrology.gov.bc.ca/ https://www.gebhardtforcolorado.com/ https://gitlab.weather.noaa.gov/ https://msoid.abom.org/ https://www.rogeebeverlyhills.com/ https://wasre-datamover.umaryland.edu/ https://worthyfigures.com/ https://www.helsingborgsakademin.helsingborg.se/ https://saa.uinsgd.ac.id/ https://designsbylillianj.com/ https://www.tsv-einheit.de/ https://starbuckspartnerhoursinfo.com/ https://infosphereeducation.com/ https://amandlaomnotho.com/ https://puntacanard.do/ https://alessandraquartaconte.com/ https://sieudaga.com/ https://horusservices.com.co/ https://tiffanyqueen.store/ https://accessstudentportal.com/ https://www.fitlifefoundations.com/ https://www.nukandy.com/ https://filipinofoodcart.com/ https://starbridgeguides.com/ https://3beansart.com/ https://www.iestpahtsihuas.edu.pe/ https://worldoffoods.net/ https://abejotaburnaby.cl/ https://peoplesopioidsummit.com/ https://voordeliggenieten.nl/ https://bewealthyandjoyful.com/ https://fabiananliker.com/ https://ipracticegolf.com/ https://lhbtiqontact.nl/ https://maxdiscountcodes.com/ https://stturtle.com/ https://clickcatalystai.com/ https://grubz.co.za/ https://ir-terrasverwarming.nl/ https://refael-group.co.il/ https://www.thedriftlesssheep.com/ https://yabolichina.com/ https://www.gr4nt.com/ https://moviestylepopcorn.com/ https://pcavisen.dk/ https://emersonart.com/ https://surfessay.com/ https://tuaton.com/ https://chelsea-westside.com/ https://jadejewlery.com/ https://sencesecret.com/ https://www.passticks.com/ https://detucasa.online/ https://davidrefael.co.il/ https://refaelgroup.co.il/ https://verygoodclean.com/ https://www.knightvisor.com/ https://klinkerhaus-am-wald.de/ https://medicata.ee/ https://refael-nadlan.co.il/ https://www.bajioffer.com/ https://buycyh.com/ https://giuseppemagra.com/ https://www.kutivzkouture.co.uk/ https://lenyvankessel.nl/ https://the-domains.com/ https://thenativeborne.com/ https://windowsandoors.co.uk/ https://max-aperture.com/ https://www.tacology101.com/ https://paragontelco.com/ https://dataleaked.com/ https://brassringlineage.co/ https://capelsoundhaven.com.au/ https://goldcoastmecfs.com/ https://sbtienda.com/ https://shehealth.com/ https://worldofteas.ca/ https://mamieexcels.com/ https://patriotluxpools.com/ https://cascadesculinary.com/ https://texasprideconcrete.com/ https://recipetohappy.com/ https://laalquiladora.com/ https://thevpsacademy.com/ https://ministry-websites.com/ https://businesswebsiteservices.net/ https://sqrealty.com.mx/ https://emrooznama.com/ https://hubbil.com/ https://seoactions.com/ https://testlang.com/ https://thevinenetwork.com/ https://yogaconmarcella.com/ https://lakehouseufaula.com/ https://elliotpro.com/ https://nftgallerycenter.com/ https://eastexhomecenter.com/ https://culturallyresponsiveminds.com/ https://leadgeeks.net/ https://nextwavestrategies.ai/ https://naju.us/ https://roofingmasters.ca/ https://smokemart.ca/ https://www.maquette.ca/ https://www.caraccidentattorneycolumbia.com/ https://www.ergotijm.nl/ https://www.earthyoga.store/ https://acesdrains.com/ https://agentedesegurosdesalud.com/ https://asportdesigns.com/ https://astatic-solutions.com/ https://beattiepropertyservices.com/ https://bigwestgiftsuite.com/ https://bleroofing.com/ https://bmugc.com/ https://cardsandcrime.com/ https://dharmasimple.com/ https://ebolightmd.com/ https://anovelidea.com.au/ https://calvaryhill-lyman.org/ https://eficon.cl/ https://divinorigen.cl/ https://einsparhelden.de/ https://bulkbuydirect.store/ https://www.caedenfetters.com/ https://www.duncandigital.com/ https://elixirclio.com/